A Low-Cost Multiplatform VLC System Prototype for Indoor Attocell Downlink Communication - Nascimento, Alaf; Costa, Wesley; Camporez, Higor; Zwaag, Klaas; Santos, Francisco; Silva, Jair (Anais do Workshop de Computação Urbana (CoUrb); 2026: Anais do X Workshop de Computação UrbanaDO - 10.5753/courb.2026.24109, 2026)
Devices operating in the Radio Frequency (RF) spectrum face capacity limitations due to licensed bandwidth and rapidly growing connectivity demand. Visible Light Communication (VLC) emerges as a complementary alternative, leveraging existing lighting infrastructure for energy-efficient indoor communication. However, for widespread adoption, VLC devices must achieve a cost comparable to established technologies. This work proposes a Plug-and-Play (PnP) USB dongle for VLC data reception based on low-cost hardware, along with a multiplatform interface for reactive data visualization. Our prototype achieves error-free downlink communication in attocell scenarios over distances up to 280 cm under line-of-sight (LOS) conditions.